2006
DOI: 10.1002/j.0022-0337.2006.70.5.tb04113.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Perceived Public Health Competency Among Recent Dental Graduates

Abstract: The aim of this study was to assess the level of self-perceived competency in dental public health in recent graduates from the Faculty of Stomatology of the Universidad Peruana Cayetano Heredia. One hundred and nineteen graduates (28.6 percent males and 71.4 percent females) were asked to rate their self-perception of proficiency on each of the twenty-one dental public health functions identified in a dental practice competency matrix. Students assessed their competence in these dental public health functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…degree is mandatory for practicing Table 1 Dental schools in Peru Table 2 Universidad Peruana Cayetano Heredia dental curriculum dentistry in Peru. The mean age of dental school graduates at the UPCH is 23.1 years (8).…”
Section: Dental School Curriculummentioning
confidence: 99%
“…degree is mandatory for practicing Table 1 Dental schools in Peru Table 2 Universidad Peruana Cayetano Heredia dental curriculum dentistry in Peru. The mean age of dental school graduates at the UPCH is 23.1 years (8).…”
Section: Dental School Curriculummentioning
confidence: 99%
“…The Institute of Medicine and the American Public Health Association ( 1 ) recommended the use of competence frameworks to inform the content of public health teaching programs. This reflected concerns about variation in the content of public health professional training programs ( 2 ), and a growing trend to competence based education in other health professions ( 3 5 ). This has resulted in an increase in the number and scope of competence frameworks for public health training and professional practice ( 1 , 6 ), along with different interpretations of such terms ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the situation of those who venture in the public sector does not seem to be different. Bernabe et. al.…”
Section: Discussionmentioning
confidence: 99%
“…al. (2006) 16 reported that recently graduated dentists considered themselves to have been insufficiently trained during their formal education for the various functions related to the practice of management in public dental care.…”
Section: Discussionmentioning
confidence: 99%